ANALYSIS OF 5C IMPLEMENTATION (CHARACTER, CAPACITY, CAPITAL, COLLATERAL AND CONDITION OF ECONOMY) IN DETERMINING THE FEASIBILITY OF CREDITIN PT. PRANK REDICAN BANKS PRIMA RIAU SENTOSA PEKANBARU - Khairunnisyah Eka Pratiwi; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
BPR is essentially a financial institution, because it has an intermediary function between those who have funds and those who need them. BPR is said to be a macro financial institution, because the main priority of its service is individuals and or small scale entrepreneurs. The purpose of this study was to analyze and find out how the implementation of 5C in the eligibility of credit applied by PT. BPR Prima Riau Sentosa Pekanbaru to prospective customers. This research was conducted at PT. BPR Prima Riau Sentosa Jl. Setia Budi No. 168-170, Rintis, fifty sub-district, pekanbaru city, riau. Types and sources of data used in this research is the key informants or(KeyInformant), Informant complementary. The method used in this research is descriptive qualitative.An assessment of the 5C implementation analysis to prospective customers conducted by PT. BPR Prima Riau Sentosa is sufficient and effective. In discussions with key informants in the evaluation 5C analysis there are three most important analytics namely Character (Character),Capital (Capital), and Collateral (Collateral). Although the dimensions of analysis from other aspects are also important and are interrelated with each other, but of the three assessments are more important and will certainly have a better impact in the future. Keywords: Procedure, 5C Analysis, Credit Worthness